2020
DOI: 10.3390/molecules25153514
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester (CAPE) Induced Apoptosis in Serous Ovarian Cancer OV7 Cells by Deregulation of BCL2/BAX Genes

Abstract: Ovarian cancer has the worst prognosis among all gynecological cancers. Therefore, it seems reasonable to seek new drugs that may improve the effectiveness of treatment or mitigate the adverse effects of chemotherapy. Caffeic acid phenethyl ester (CAPE) has many beneficial biological properties. The aim of the study was to assess the anticancer properties of CAPE against serum ovarian carcinoma cells. The morphology of the cells was evaluated in H-E staining and in transmission electron microscopy. The cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Although many proteins can regulate apoptosis through cascade reactions, the Bax/Bcl-2 ratio plays a vital role in regulating apoptosis [31]. Caffeic acid phenethyl ester can control the balance between Bax/Bcl-2 and induce the apoptosis of the ovarian cancer OV7 cells to play an antitumor role [32]. Gambogic acid [30,33] and gallic acid [29] can upregulate the Bax protein expression and downregulate the Bcl-2 protein expression, inducing tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although many proteins can regulate apoptosis through cascade reactions, the Bax/Bcl-2 ratio plays a vital role in regulating apoptosis [31]. Caffeic acid phenethyl ester can control the balance between Bax/Bcl-2 and induce the apoptosis of the ovarian cancer OV7 cells to play an antitumor role [32]. Gambogic acid [30,33] and gallic acid [29] can upregulate the Bax protein expression and downregulate the Bcl-2 protein expression, inducing tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies demonstrated that CA and its derivatives (among numerous other potential therapeutic properties) are compounds with potent anticancer effects. In vitro experiments have revealed their cytotoxic properties inter alia on breast [ 64 , 65 ], ovarian [ 66 , 67 ], colon [ 68 , 69 , 70 , 71 ], hepatoma [ 72 , 73 , 74 ], melanoma [ 75 , 76 , 77 ], prostate [ 78 ] and pancreatic [ 30 , 31 , 79 ] cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a remarkable decrease in the cell viability, migration, and invasion of SKOV-3 accompanied by an obstructed Ki67 and PCNA expression, nuclear translocation of p65, inhibition of IκB phosphorylation, and NF-κB p65 DNA binding activity in the CAPE treated cells [ 137 ]. In another study, Kleczka et al [ 138 ] reported significant cytotoxicity, decreased lysosomal activity, and the total synthesis of cellular proteins in CAPE-treated OV7 serum ovarian cancer cells. Moreover, this study also reported a CAPE-induced apoptosis via dysregulation of Bax/Bcl-2 balance [ 138 ].…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
“…In another study, Kleczka et al [ 138 ] reported significant cytotoxicity, decreased lysosomal activity, and the total synthesis of cellular proteins in CAPE-treated OV7 serum ovarian cancer cells. Moreover, this study also reported a CAPE-induced apoptosis via dysregulation of Bax/Bcl-2 balance [ 138 ].…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%